Comparison of Brokerage and Commission in Iranian Commercial Law - Ghadami, Manochehr; Jebelli, Ali Radan (Journal of History Culture and Art Research, 2017)
Terms such as commission and brokerage are similar in the concept of agency and in some cases they are different. In the legal system of Iran, commission section is derived from French law and it drives out the commission from the realm of agency and justifies it as an entity equal to the contract of the mandate. On the other hand, the brokerage has not been discussed in Iran’s jurisprudential sources and civil law as a legal body establishment; therefore, we can take it as new found phenomena that came to our legal system simultaneous with the commercial law concepts. Such differences between commission agent with broker can be stated like this: the commission agent is only obliged to announce the actions and especially do his missions to the commander, in fact the commission agent has the right of disclosure before his commander, but according to the article 337 of the written law, the broker also has the right of disclosure of the details of transaction toward the party with whom the brokerage contract has not been signed. The broker is usually the middleman of the transmission in consideration of receiving a specific amount of money or he can find a party for a person who wants to conduct a transaction and he himself doesn’t get involved in the transaction and is not engaged, whereas the commission agent is directly a contracting party and the true beneficiary (commander) which the transaction is done in his account has no contact with the main buyer. This survey is done by the analytical-descriptive method for comparing the brokerage and commission in the commercial law of Iran.